PENINGKATAN PERILAKU SANGGING DALAM PROSESI POTONG GIGI DI KECAMATAN KUTA UTARA, BADUNG, BALI - Ida Ayu Dewi Kumala Ratih; Sagung Agung Putri Dwiastuti; Ida Bagus Wiryanatha (UNHI Press, 2023)
Sangging is someone who performs a tooth-cutting ceremony. Sangging tools are used come into contact with saliva. If it is not carried out according to health rules, it can have a detrimental impact. The intended detrimental impact is that people can contract hepatitis, HIV/AIDS, sexually transmitted diseases such as syphilis, tuberculosis, herpes and fungal infections. The following problems are known: lack of tool sterility, Sangging has not paid attention to personal protective equipment, there is a tendency for HIV / AIDS sufferers to increase in Bali, the Covid-19 pandemic. The solutions offered are: education on disease transmission that can occur through dental cutting, personal protective equipment, sterilization of the tools, use of disposable tools.The test results with Mann Whitney obtained sig. 0.308 indicates that there is no significant difference between the results of the self-assessment of Sangging behavior between pretest and posttest. This can happen considering that most of Sangging's behavior is very good, except for the ability to sterilize tools because Sangging needs a companion to sterilize tools, the success of socialization about Health Programs during a pandemic. The implementation of community service activities in North Kuta District is going well and it can be concluded that: Sangging behavior is increasing.